Qualidade interna e externa de ovos de codornas japonesas armazenados em diferentes temperaturas e períodos de estocagem - Marinho, Andreza Lourenço (2011)
With the aim of evaluating the internal and external of eggs of quality quail stored under refrigeration and at room temperature, we used 440 eggs Japanese quail collected after laying. The eggs were distributed in a completely randomized design in factorial 2x11 (2 storage temperature x 11 storage periods) with 20 repetitions. Analyses were performed on eggs at 0, 3, 6, 9, 12, 15, 18, 21, 24, 27 and 30 days of storage. The variables analyzed were weight loss (%), specific gravity (g / ml), yolk index and albumen percentages (%) of yolk, albumen and shell, shell thickness (mm), yolk color, pH albumen and yolk and Haugh Unit. Statistical analysis was performed using the System Analysis Statistical and Genetic (SAEG) and means compared by Newman Keuls test at 5% probability. Observed effect was (P<0,05) linear weight loss of eggs (%), specific gravity (g / ml), yolk index, albumen index, albumen percentage, yolk percentage, pH and yolk Haugh unit, in both storage temperatures. However, the pH of the albumen had an effect (P<0,05) quadratic for eggs stored at both storage temperatures. To eggshell percentage, shell thickness and yolk color not found a significant effect (P>0,05) among treatments. We conclude that Japanese quail eggs can be stored for up to 18 days at room temperature and 30 days under refrigeration.